Expanding agency: The mapping of architectural design discourse in Indonesia's academic publications - Mikhael Johanes (ARSNET, 2021)
Architectural academic publications are essentials elements in defining and establishing the architecture academic discourses in institutional context. A critical, retrospective reading of past and present architectural publications could reveal the current development of the field and provide an empirical basis for future actions. This paper digitally maps the notion of ‘design’ within the published articles in Indonesian architectural journals from the past decade to understand the current situation and present the country’s challenges in developing the architectural design discourse. Through consideration of architectural academic journals’ role in establishing the field’s boundary, a bibliometric mapping was performed on a corpus of 1031 abstracts collected from prominent Indonesian architectural journals. This paper reflects on the extracted key terms from the corpus through different mapping strategies using bibliometric analysis methods. From the mapping findings, and by extending the notion of design as a transformative agency in architecture, this paper retrospectively suggests a more diverse, creative, and provocative development of design discourse in Indonesian architectural academic scholarship.